(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper explores the critical intersection of disability studies and trauma theory, offering a new framework for understanding the lived experiences of women who face overlapping systems of oppression. Historically, dominant trauma narratives have often pathologized women’s embodied experiences, failing to contextualize them within the broader socio-political structures that cause harm. By integrating contemporary feminist disability studies with trauma theory, this study aims to challenge these deficit-oriented models and center women’s agency, resistance, and narrative sovereignty. The paper’s theoretical framework is built on three key pillars. Feminist Disability Theory critiques the medicalized view of disability, instead emphasizing the social, political, and cultural contexts that create disabling conditions. Trauma Theory analyzes the psychological, social, and physical impacts of violence, oppression, and systemic inequality. The combined lens of these two fields is viewed through intersectionality, a framework that reveals how identities such as gender, disability, race, and class interact to shape both vulnerability to trauma and pathways to healing. By combining these perspectives, the study highlights the necessity of moving beyond an individual focus on pathology toward a systemic, humanizing approach to understanding trauma. It examines the ways in which these fields converge, discusses current trends and challenges in their integration, and identifies emerging thematic areas that require further exploration. This research is a crucial step toward developing more holistic and equitable approaches in both scholarly and clinical practice.